2012
DOI: 10.1002/pros.22504
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive auto‐regulation of androgen receptor provides a paradigm shifting rationale for bipolar androgen therapy (BAT) for castrate resistant human prostate cancer

Abstract: Cell culture/xenograft and gene arrays of clinical material document that development of castration resistant prostate cancer (CRPC) cells involves acquisition of adaptive auto-regulation resulting in > 25 fold increase in Androgen Receptor (AR) protein expression in a low androgen environment. Such adaptive AR increase paradoxically is a liability in castrated hosts; however, when supraphysiologic androgen is acutely replaced. Cell synchronization/anti-androgen response document this is due to AR binding to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
103
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 94 publications
(114 citation statements)
references
References 38 publications
1
103
1
2
Order By: Relevance
“…The findings might help explain why a new paradigm for treating patients with PCa, referred to as bipolar ADT (67), in which patients undergoing chemotherapy cycle through ADT followed by a supraphysiological dose of androgen, proved more beneficial than ADT alone. Because the function of AR in DNA replication is to help repair double-strand breaks, it has been argued that binding of testosterone to AR under supraphysiological conditions could prevent its normal function of repairing double-strand breaks, which, in turn, can lead to cell cycle failure and programmed cell death (43,68), as seen in patients who responded to bipolar ADT. However, it has also been reported by others (69) that supraphysiological levels of androgens can induce cell cycle arrest and up-regulate markers of cellular senescence in human PCa cells.…”
Section: Discussionmentioning
confidence: 99%
“…The findings might help explain why a new paradigm for treating patients with PCa, referred to as bipolar ADT (67), in which patients undergoing chemotherapy cycle through ADT followed by a supraphysiological dose of androgen, proved more beneficial than ADT alone. Because the function of AR in DNA replication is to help repair double-strand breaks, it has been argued that binding of testosterone to AR under supraphysiological conditions could prevent its normal function of repairing double-strand breaks, which, in turn, can lead to cell cycle failure and programmed cell death (43,68), as seen in patients who responded to bipolar ADT. However, it has also been reported by others (69) that supraphysiological levels of androgens can induce cell cycle arrest and up-regulate markers of cellular senescence in human PCa cells.…”
Section: Discussionmentioning
confidence: 99%
“…In the setting of castrationresistance, prostate cancer cells significantly elevate levels of AR expression as an adaptive mechanism, in order to continue to express the androgen-regulated genes needed for growth [48]. In the setting of amplified AR levels, flooding the cell with supraphysiological levels of testosterone can paradoxically result in cell-cycle arrest and double-strand DNA breaks [49]. In vivo models have shown that tumors can regress with the administration of high-dose testosterone therapy, but eventually tumors re-adapt to the high testosterone environment over time [50].…”
Section: Treatment Opportunities For Homologous Recombination-deficiementioning
confidence: 99%
“…Gao and colleagues (41) described the role of AR as a tumor suppressor in castration-resistant prostate cancer (CRPC) cells by inhibiting DNA replication-related genes via the recruitment of hypophosphorylated Rb. In addition, the clinical and preclinical efficacy seen with high-dose androgen therapy in CRPC was also attributed to androgen-induced stabilization of AR, which prevents the relicensing of DNA for replication and subsequent cell-cycle progression (58,59). In the current study, the AR-mediated suppression of ESR1 and its downstream pathway, along with the suppression of DNA replication-and cell cycle-related genes seen with RAD140 treatment suggest a distinct mechanism of action of this SARM in AR/ER þ breast cancer cells.…”
Section: Sarm Inhibits Ar/ermentioning
confidence: 99%